Thermal barrier coating material, thermal barrier coating and preparation method

By continuously resolving zirconia in hafnium oxide and doping yttrium element, the problem of structural instability of ZrO2 thermal barrier coating at high temperatures is solved, the high temperature resistance and sintering resistance of thermal barrier coating are improved, and the advanced aero engines are met Highly efficient thermal insulation and long life requirements.

CN119220923APending Publication Date: 2024-12-31GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411342567.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The current 6-8 wt%Y2O3 stable ZrO2 thermal barrier coating is structurally unstable in high-temperature service environments, resulting in cracks and peeling, making it difficult to meet the high pushing force and long service life requirements of advanced aircraft engines.

Method used

Through continuous solid solution of zirconia by hafnium oxide and binary rare earth doping of yttrium and ytterbium, the high temperature resistance and sintering resistance of the thermal barrier coating are improved, and the stability of the t' phase of the traditional YSZ coating is maintained.

Benefits of technology

It improves the thermodynamic properties and sintering resistance of the thermal barrier coating, reduces thermal conductivity, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220923A_ABST
    Figure CN119220923A_ABST
Patent Text Reader

Abstract

The invention relates to a thermal barrier coating material, a thermal barrier coating and a preparation method, the thermal barrier coating material comprises binary rare earth doped zirconium-hafnium oxide solid solution powder, and the binary rare earth doped elements are yttrium element and ytterbium element. Zirconium oxide is subjected to continuous solid solution through hafnium oxide, so that the high-temperature resistance of the thermal barrier coating can be improved, and the melting point and the phase transformation temperature of the thermal barrier coating are improved. Through binary rare earth doping of the yttrium element and the ytterbium element, the synergistic effect of the yttrium element and the ytterbium element is exerted, the thermodynamic property is improved, meanwhile, the anti-sintering performance of the thermal barrier coating can be improved, and the thermal conductivity of the thermal barrier coating is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal barrier coatings, in particular to a thermal barrier coating material, a thermal barrier coating and a preparation method thereof. Background Art

[0002] Thermal barrier coating is an important thermal insulation and protective ceramic coating. It is deposited on the surface of high-temperature resistant metals or superalloys, causing a large temperature drop when high-temperature combustion gas reaches the metal parts, reducing the temperature of the base material, thereby increasing the operating temperature and service life of the hot end components of the aircraft engine and the thermal efficiency of the power system.

[0003] At present, the 6-8wt% Y2O3 partially stabilized ZrO2 (classic YSZ) thermal barrier coating in service basically meets the material selection requirements of the ceramic surface layer of thermal barrier coatings because of its advantages such as low thermal conductivity, high fracture toughness and high thermal expansion coefficient. The reason why the classic YSZ coating has been so popular for a long time is that it has a single metastable tetragonal t' phase that is not in thermodynamic equilibrium and does not transform. The t' phase is a transition phase between the t phase and the c phase. Its unique ferroelastic domain structure and its toughening mechanism make the YSZ coating still have good fracture toughness at high temperatures. However, since the t' phase is metastable, when the coating is in a high-temperature service environment above 1200℃ for a long time, the structural stabilizer Y2O3 will diffuse, thereby generating a Y2O3-rich c phase and a Y2O3-poor t phase. Subsequently, during the cooling process, the t phase will transform into the m phase, undergoing a martensitic phase transformation, accompanied by a 3-5% volume expansion, resulting in an increase in the internal stress of the coating and a large number of microcracks, resulting in large-area cracking and peeling, which leads to the failure of the YSZ coating. Secondly, YSZ coating is prone to sintering during high-temperature service above 1200°C, which makes the coating densified and increases the Young's modulus, resulting in reduced thermal insulation and thermal shock resistance of the YSZ coating. Therefore, it is difficult to meet the development of advanced aircraft engine propulsion engines towards high thrust and long service life.

[0004] So far, although researchers have conducted relevant research on YSZ-modified and rare earth-modified zirconium / hafnium / cerium / tantalum / niobium-based oxide thermal barrier coating systems, the comprehensive performance of the new thermal barrier coatings lacks obvious advantages over the classic YSZ thermal barrier coatings. Therefore, the improvement of the comprehensive performance of the current thermal barrier coatings and the exploration of new thermal barrier coating systems are still the current research focus. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a thermal barrier coating material, a thermal barrier coating and a preparation method thereof. The method improves the high temperature resistance of the thermal barrier coating itself by continuously dissolving hafnium oxide in zirconium oxide, and uses binary rare earth doping of yttrium and ytterbium elements to achieve the stability of the t' phase structure. The prepared thermal barrier coating can retain the t' phase of the traditional YSZ coating while having better thermodynamic properties and more excellent sintering resistance.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a thermal barrier coating material, comprising a binary rare earth doped zirconium-hafnium oxide solid solution powder, wherein the binary rare earth doping elements are yttrium and ytterbium.

[0008] The present invention can improve the high temperature resistance of the thermal barrier coating by continuously dissolving hafnium oxide in zirconium oxide, and improve the melting point and phase transition temperature of the thermal barrier coating. By doping binary rare earth elements of yttrium and ytterbium, the synergistic effect of the two elements is exerted to improve the thermodynamic properties while also improving the anti-sintering performance of the thermal barrier coating and reducing the thermal conductivity of the thermal barrier coating.

[0009] Preferably, the chemical formula of the thermal barrier coating material is (Zr 0.5 Hf 0.5 ) 0.9 (Y 1-x Yb x ) 0.1 O 1.95 , wherein 0.1≤x≤0.5, for example, x can be 0.1, 0.2, 0.3, 0.4, 0.45 or 0.5, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0010] The present invention will Y 3+ and Yb 3+ After ion doping into the zirconium-hafnium oxide solid solution lattice, Y 3+ and Yb 3+ Ions will replace Zr 4+ and Hf 4+ ions, resulting in lattice distortion and a certain amount of oxygen vacancies, which is beneficial to improve the stability of the t' phase and further reduce the thermal conductivity. 3+ and Yb 3+ The difference in ion radius leads to different distortions after entering the lattice. Therefore, the present invention can optimize Y 3+ and Yb 3+ The doping amount between ions can be further optimized to further optimize the thermal conductivity and anti-sintering performance of the thermal barrier coating.

[0011] In a second aspect, the present invention provides a method for preparing the thermal barrier coating material as described in the first aspect, the preparation method comprising the following steps:

[0012] First, a zirconium source, a hafnium source, a yttrium source, a ytterbium source and a solvent are mixed, a precipitant is added dropwise, the mixture is aged, and then a precipitate is obtained by filtering. The precipitate is calcined to obtain the thermal barrier coating material.

[0013] Preferably, the zirconium source includes any one of zirconium oxychloride, zirconium chloride or zirconium nitrate, or a combination of at least two of them. Typical but non-limiting combinations include a combination of zirconium oxychloride and zirconium chloride, or a combination of zirconium oxychloride, zirconium chloride and zirconium nitrate.

[0014] Preferably, the hafnium source includes any one of hafnium chloride, hafnium oxychloride or hafnium nitrate, or a combination of at least two of them. Typical but non-limiting combinations include a combination of hafnium chloride and hafnium oxychloride, or a combination of hafnium chloride, hafnium oxychloride and hafnium nitrate.

[0015] Preferably, the yttrium source includes any one of yttrium oxide, yttrium chloride or yttrium nitrate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of yttrium oxide and yttrium chloride, or a combination of yttrium oxide, yttrium chloride and yttrium nitrate.

[0016] Preferably, the ytterbium source includes any one of ytterbium oxide, ytterbium chloride or ytterbium nitrate, or a combination of at least two of them. Typical but non-limiting combinations include a combination of ytterbium oxide and ytterbium chloride, or a combination of ytterbium oxide, ytterbium chloride and ytterbium nitrate.

[0017] Preferably, the stoichiometric ratio of the zirconium source, hafnium source, yttrium source and ytterbium source is (0.45):(0.45):(0.05-0.09):(0.01-0.05), for example, it can be 0.45:0.45:0.09:0.01, 0.45:0.45:0.08:0.02, 0.45:0.45:0.07:0.03, 0.45:0.45:0.06:0.04 or 0.45:0.45:0.05:0.05, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] Preferably, the temperature of the first mixing is 80-100°C, for example, 80°C, 85°C, 90°C, 95°C or 100°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] Preferably, the solvent comprises deionized water.

[0020] Preferably, the precipitant comprises aqueous ammonia.

[0021] Preferably, the pH value of the precipitant is 13-14, for example, 13, 13.2, 13.4, 13.6, 13.8 or 14, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0022] Preferably, the aging time is 12-24 hours, for example, it can be 12 hours, 14 hours, 16 hours, 18 hours, 20 hours or 24 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] Preferably, washing is further included after aging and before filtering.

[0024] Preferably, the washing detergent is deionized water.

[0025] Preferably, the washing is performed 5-7 times, for example, 5 times, 6 times or 7 times.

[0026] Preferably, the end point of the washing is to make the pH value of the washing liquid 8-9, for example, it can be 8, 8.2, 8.4, 8.6, 8.8 or 9, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the filtering comprises suction filtration.

[0028] Preferably, after filtering and before calcining, washing and drying are also performed in sequence.

[0029] Preferably, the cleaning includes cleaning with deionized water and ethanol for 3-5 times respectively, for example, it can be cleaning with deionized water for 3 times and cleaning with ethanol for 3 times, cleaning with deionized water for 4 times and cleaning with ethanol for 4 times, or cleaning with deionized water for 5 times and cleaning with ethanol for 5 times, but is not limited to the listed cases.

[0030] Preferably, the drying comprises oven drying.

[0031] Preferably, the drying temperature is 60-80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] Preferably, the drying time is 10-12 h, for example, 10 h, 10.5 h, 11 h, 11.5 h or 12 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0033] Preferably, grinding and a first screening are further performed after drying and before calcining.

[0034] Preferably, the mesh size of the first sieving is 150-250 meshes, for example, 150 meshes, 180 meshes, 200 meshes, 230 meshes or 250 meshes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] Preferably, the calcination temperature is 1000-1200°C, for example, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0036] Preferably, the calcination time is 2-4 h, for example, 2 h, 2.5 h, 3 h, 3.5 h or 4 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] During the calcination process, the present invention adjusts the calcination temperature and time to dope rare earth ions into the lattice of the zirconium-hafnium solid solution to form a t-phase powder. Within the preferred calcination temperature and time range, the prepared thermal barrier coating material has a stable single tetragonal t-phase.

[0038] In a third aspect, the present invention provides a thermal barrier coating, wherein raw materials for preparing the thermal barrier coating include the thermal barrier coating material described in the first aspect.

[0039] In a fourth aspect, the present invention provides a method for preparing the thermal barrier coating according to the third aspect, the preparation method comprising the following steps:

[0040] secondly mixing the thermal barrier coating material, the binder and the dispersant, sintering to obtain a spraying powder, and performing atmospheric plasma spraying on the spraying powder to obtain the thermal barrier coating;

[0041] The thermal barrier coating material is the thermal barrier coating material described in the first aspect.

[0042] Preferably, the amount of the binder is 10-20wt% of the thermal barrier coating material, for example, it can be 10wt%, 12wt%, 14wt%, 16wt%, 18wt% or 20wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] Preferably, the amount of the dispersant is 10-20wt% of the thermal barrier coating material, for example, it can be 10wt%, 12wt%, 14wt%, 16wt%, 18wt% or 20wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] Preferably, a second screening is performed after the second mixing and before sintering.

[0045] Preferably, the mesh size of the second sieving is 180-400 mesh, for example, it can be 180 mesh, 200 mesh, 250 mesh, 300 mesh, 350 mesh or 400 mesh, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] Preferably, the sintering temperature is 1100-1300°C, for example, 1100°C, 1150°C, 1200°C, 1250°C or 1300°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0047] Preferably, the sintering time is 2-3 h, for example, 2 h, 2.2 h, 2.5 h, 2.8 h or 3 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0048] During the sintering process, the present invention removes moisture from the binder and powder by regulating the sintering temperature and time, further increasing the stability of the powder and the bonding strength between large and small particles, further optimizing the fluidity and bulk density of the powder after granulation, and facilitating the subsequent atmospheric plasma spraying process.

[0049] Preferably, the bulk density of the spray powder is 1.7-3 g / cm 3 , for example, it can be 1.7 g / cm 3 , 2g / cm 3 , 2.5g / cm 3 , 2.8g / cm 3 or 3g / cm 3 , but not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0050] Preferably, the fluidity of the spray powder is 20-55s / 50g, for example, it can be 20s / 50g, 30s / 50g, 40s / 50g, 50s / 50g or 55s / 50g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] The fluidity test of the powder for spraying of the present invention refers to GB / T 1482-2010 "Standard Funnel Method for Determination of Fluidity of Metal Powders (Hall Rheometer)". The test method for the fluidity of the powder for spraying is: weigh 50g of the powder for spraying and put it into the funnel of the Hall Rheometer, and measure the time for 50g of powder to flow through a standard funnel with a pore size of 2.5mm. The shorter the time, the better the fluidity (unit is s / 50g).

[0052] The bulk density test of the spray powder of the present invention is measured in accordance with GB / T 1479.1-2011 "Determination of bulk density of metal powders Part 1: Funnel method". The specific operation is as follows: the spray powder is loaded into the funnel of the Hall flow meter, and the powder is allowed to flow freely from the small hole at the bottom of the funnel to the 25 cm at the bottom. 3 Standard container, weigh the mass of powder used to fill the container, and calculate the bulk density (in g / cm 3 ).

[0053] The final results of bulk density and fluidity are taken from the average of more than three measurements to reduce errors.

[0054] Preferably, the spray gun voltage of the atmospheric plasma spraying is 60-80V, for example, 60V, 65V, 70V, 75V or 80V, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0055] Preferably, the spray gun current of the atmospheric plasma spraying is 550-650A, for example, 550A, 580A, 600A, 620A or 650A, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0056] Preferably, the hydrogen flow rate of the atmospheric plasma spraying is 35-60 L / h, for example, 35 L / h, 40 L / h, 45 L / h, 50 L / h or 60 L / h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0057] Preferably, the argon flow rate of the atmospheric plasma spraying is 1500-2500 L / h, for example, 1500 L / h, 1800 L / h, 2000 L / h, 2200 L / h or 2500 L / h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] Preferably, the spraying distance of the atmospheric plasma spraying is 90-120 mm, for example, 90 mm, 95 mm, 100 mm, 110 mm or 120 mm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0059] Preferably, the powder feeding rate of the atmospheric plasma spraying is 30-50 g / min, for example, it can be 30 g / min, 35 g / min, 40 g / min, 45 g / min or 50 g / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0061] (1) first mixing a zirconium source, a hafnium source, a yttrium source and a ytterbium source according to a stoichiometric ratio, and then adding a solvent to obtain a clear solution;

[0062] The temperature of the first mixing is 80-100°C;

[0063] (2) adding the clarified solution in step (1) dropwise to a precipitant, aging for 12-24 hours, washing with deionized water 5-7 times, wherein the pH of the washing solution after washing is 8-9, and obtaining a white colloidal precipitate;

[0064] (3) filtering the white colloidal precipitate obtained in step (2), and then washing it with deionized water and ethanol for 3-5 times respectively to obtain a precipitate;

[0065] (4) drying the precipitate obtained in step (3) at 60-80° C. for 10-12 h, and then grinding, first screening and calcining in sequence to obtain a thermal barrier coating material;

[0066] The mesh size of the first sieve is 150-250 mesh; the calcination temperature is 1000-1200° C., and the calcination time is 2-4 hours;

[0067] (5) The thermal barrier coating material, binder and dispersant obtained in the second mixing step (4) are sequentially screened and sintered to obtain a powder for spraying;

[0068] The mesh number of the second sieve is 180-400 mesh; the sintering temperature is 1100-1300°C, and the sintering time is 2-3h; the bulk density of the spray powder is 1.7-3g / cm 3 , fluidity is 20-55s / 50g;

[0069] (6) subjecting the spraying powder obtained in step (5) to atmospheric plasma spraying to obtain the thermal barrier coating;

[0070] The spray gun voltage of the atmospheric plasma spraying is 60-80V, the spray gun current is 550-650A, the hydrogen flow rate is 35-60L / h, the argon flow rate is 1500-2500L / h, the spraying distance is 90-120mm, and the powder feeding rate is 30-50g / min.

[0071] Compared with the prior art, the present invention has at least the following beneficial effects:

[0072] (1) The thermal barrier coating prepared by the present invention continuously dissolves ZrO2 in HfO2, thereby improving the high temperature resistance of the thermal barrier coating itself, and further increasing the melting point and phase transition temperature of the thermal barrier coating;

[0073] (2) The thermal barrier coating prepared by the present invention uses binary rare earth doping of yttrium and ytterbium to achieve stabilization of the t' phase structure, while retaining the existence form of the t' phase of the traditional YSZ thermal barrier coating, and has better thermodynamic properties and more excellent anti-sintering performance;

[0074] (3) The present invention adopts chemical co-precipitation-calcination method and atmospheric plasma spraying to prepare thermal barrier coating. This method is simple and easy to operate, has low cost and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 Full spectrum X-ray diffraction patterns of thermal barrier coating materials prepared in Example 1, Examples 4-5, and Comparative Example 1 of the present invention, commercial YSZ thermal barrier coating materials, and PDF standard cards of t-ZrO2, t-HfO2, Y2O3, and Yb2O3;

[0076] Figure 2 It is the Raman graph of the thermal barrier coating material prepared in Example 1, Examples 4-5, and Comparative Example 1 of the present invention and the commercial YSZ thermal barrier coating material;

[0077] Figure 3 The 10-80° full spectrum X-ray diffraction patterns of the thermal barrier coatings prepared in Application Example 1, Application Examples 4-5, Comparative Application Example 1 and Comparative Application Example 3 of the present invention;

[0078] Figure 4 It is a 27-33° micro-area X-ray step-scanning diffraction pattern of the thermal barrier coating prepared in Application Example 1, Application Examples 4-5, Comparative Application Example 1 and Comparative Application Example 3 of the present invention;

[0079] Figure 5 It is a 72-76° micro-area X-ray step-scanning diffraction pattern of the thermal barrier coating prepared in Application Example 1, Application Examples 4-5, Comparative Application Example 1 and Comparative Application Example 3 of the present invention;

[0080] Figure 6 Raman images of thermal barrier coatings prepared in Application Example 1, Application Examples 4-5, Comparative Application Example 1 and Comparative Application Example 3 of the present invention;

[0081] Figure 7 This is a differential scanning calorimetry (TG-DSC) curve of the thermal barrier coating prepared in Application Example 1 of the present invention;

[0082] Figure 8 This is a differential scanning calorimetry (TG-DSC) curve of the thermal barrier coating prepared in Application Example 4 of the present invention;

[0083] Fig. 9 This is a differential scanning calorimetry (TG-DSC) curve of the thermal barrier coating prepared in Application Example 5 of the present invention;

[0084] Fig.10 This is a differential scanning calorimetry (TG-DSC) curve of the thermal barrier coating prepared in Comparative Application Example 1 of the present invention;

[0085] Fig.11 This is a differential scanning calorimetry (TG-DSC) curve of the thermal barrier coating prepared in comparative application example 3 of the present invention;

[0086] Fig.12 The thermal conductivity of the thermal barrier coating prepared in Application Example 1, Application Examples 4-5, Comparative Application Example 1 and Comparative Application Example 3 of the present invention varies with temperature;

[0087] Fig.13 This is a graph showing the density of the thermal barrier coatings prepared in Application Example 1, Application Examples 4-5, Comparative Application Example 1 and Comparative Application Example 3 of the present invention as a function of annealing time at 1500°C. DETAILED DESCRIPTION

[0088] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0089] The commercial YSZ powder used below was purchased from the Institute of Process Engineering, Chinese Academy of Sciences. The product brand is CM60 and the product batch number is 2022-01.

[0090] Example 1

[0091] This embodiment provides a thermal barrier coating material, and a preparation method of the thermal barrier coating material comprises the following steps:

[0092] (1) According to the stoichiometric ratio, 60.8570 g of HfCl4 was weighed into a beaker, and 700 mL of deionized water was added to dissolve it. Then, 61.2275 g of ZrOCl2·8H2O, 3.9408 g of Yb2O3, and 2.2581 g of Y2O3 were weighed into the beaker. The mixture was heated at 90°C with magnetic stirring until the solution became clear, and then the solution was cooled to room temperature.

[0093] (2) slowly adding the clarified solution in step (1) dropwise into ammonia water with a pH of 13 through a separatory funnel, controlling the dripping rate to 2 drops / s, starting stirring, generating a white colloidal precipitate, and aging for 24 hours, then washing the precipitate with deionized water 6 times to remove impurity ions, the pH of the washing solution after washing is 8, and obtaining a white colloidal precipitate;

[0094] (3) The precipitate obtained in step (2) was filtered and washed with deionized water and anhydrous ethanol three times respectively, and the washed precipitate was placed in an oven at 80° C. and dried for 12 h;

[0095] (4) grinding the precipitate obtained in step (3), passing it through a 200-mesh sieve, and calcining it at 1000° C. for 2 h to obtain the thermal barrier coating material;

[0096] The chemical formula of the thermal barrier coating material is (Zr 0.5 Hf 0.5 ) 0.9 (Y 0.5 Yb 0.5 ) 0.1 O 1.95 , and recorded as 5YbYSHZ.

[0097] Example 2

[0098] This embodiment provides a thermal barrier coating material, and a preparation method of the thermal barrier coating material comprises the following steps:

[0099] (1) 50.4239 g HfOCl2 was weighed into a beaker according to the stoichiometric ratio, and 1000 mL deionized water was added to dissolve it. Then 44.2746 g ZrCl4, 0.5588 g YbCl3 and 3.5146 g YCl3 were weighed into the beaker, and heated at 80 °C with magnetic stirring until the solution became clear, and then the solution was cooled to room temperature;

[0100] (2) slowly adding the clarified solution in step (1) dropwise into ammonia water with a pH of 14 through a separatory funnel, controlling the dripping rate to 1 drop / s, starting stirring to generate a white colloidal precipitate, and aging for 12 hours, then washing the precipitate with deionized water 7 times to remove impurity ions, the pH of the washing solution after washing is 9, and obtaining a white colloidal precipitate;

[0101] (3) The precipitate obtained in step (2) was filtered and washed with deionized water and anhydrous ethanol four times respectively, and the washed precipitate was placed in an oven at 60° C. and dried for 10 h;

[0102] (4) grinding the precipitate obtained in step (3), passing it through a 150-mesh sieve, and calcining it at 1000° C. for 4 h to obtain the thermal barrier coating material;

[0103] The chemical formula of the thermal barrier coating material is (Zr 0.5 Hf 0.5 ) 0.9 (Y 0.9 Yb 0.1 ) 0.1 O 1.95 .

[0104] Example 3

[0105] This embodiment provides a thermal barrier coating material, and a preparation method of the thermal barrier coating material comprises the following steps:

[0106] (1) According to the stoichiometric ratio, 81.0361 g of Hf(NO3)4 was weighed into a beaker, and 600 mL of deionized water was added to dissolve it. Then, 64.4556 g of Zr(NO3)4, 3.5906 g of Yb(NO3)3, and 2.7492 g of Y(NO3)3 were weighed into a beaker, and heated at 100 °C with magnetic stirring until the solution became clear, and then the solution was cooled to room temperature;

[0107] (2) slowly adding the clarified solution in step (1) dropwise into aqueous ammonia with a pH of 13.5 through a separatory funnel, controlling the dripping rate to 3 drops / s, starting stirring, generating a white colloidal precipitate, and aging for 18 hours, then washing the precipitate with deionized water 5 times to remove impurity ions, the pH of the washing solution after washing being 8.5, and obtaining a white colloidal precipitate;

[0108] (3) The precipitate obtained in step (2) was filtered and washed with deionized water and anhydrous ethanol five times each, and the washed precipitate was placed in an oven at 70° C. and dried for 12 h;

[0109] (4) grinding the precipitate obtained in step (3), passing it through a 250-mesh sieve, and calcining it at 1200° C. for 2 h to obtain the thermal barrier coating material;

[0110] The chemical formula of the thermal barrier coating material is (Zr 0.5 Hf 0.5 ) 0.9 (Y 0.5 Yb 0.5 ) 0.1 O 1.95 .

[0111] Example 4

[0112] The only difference between this embodiment and embodiment 1 is that, except for step (1) using 2.3645 g Yb2O3 and 3.1613 g Y2O3, the rest is the same as embodiment 1.

[0113] The chemical formula of the thermal barrier coating material is (Zr 0.5 Hf 0.5 ) 0.9 (Y 0.7 Yb 0.3 ) 0.1 O 1.95 , and recorded as 3YbYSHZ.

[0114] Example 5

[0115] The only difference between this embodiment and embodiment 1 is that, except for step (1) using 0.7882 g Yb2O3 and 4.0646 g Y2O3, the rest is the same as embodiment 1.

[0116] The chemical formula of the thermal barrier coating material is (Zr 0.5 Hf 0.5 ) 0.9 (Y 0.9 Yb 0.1 ) 0.1 O 1.95 , and recorded as 1YbYSHZ.

[0117] Example 6

[0118] The only difference between this embodiment and embodiment 1 is that, except for the calcination temperature of step (4) being 950° C., the rest is the same as embodiment 1.

[0119] Example 7

[0120] The only difference between this embodiment and embodiment 1 is that, except for the calcination temperature of step (4) being 1250° C., the rest is the same as embodiment 1.

[0121] Comparative Example 1

[0122] The difference between this comparative example and Example 1 is that, except for the use of 7.8816 g of Yb2O3 in step (1), the rest is the same as Example 1.

[0123] The chemical formula of the thermal barrier coating material is (Zr 0.5 Hf 0.5 ) 0.9 Yb 0.1 O 1.95 , and recorded as 10YbSHZ.

[0124] Figure 1 Full spectrum X-ray diffraction patterns of thermal barrier coating materials prepared in Example 1, Examples 4-5, and Comparative Example 1 of the present invention, commercial YSZ thermal barrier coating materials, and PDF standard cards of t-ZrO2, t-HfO2, Y2O3, and Yb2O3; Figure 2 The Raman graphs of the thermal barrier coating materials prepared in Example 1, Examples 4-5, and Comparative Example 1 of the present invention and the commercial YSZ thermal barrier coating material are shown in the figure. It can be seen from the figure that the prepared thermal barrier coating materials do not have diffraction peaks of rare earth oxides Yb2O3 and Y2O3. Figure 2 The Raman spectrum proves that the powder contains only a single tetragonal t phase diffraction peak and does not contain m phase.

[0125] Comparative Example 2

[0126] The difference between this comparative example and Example 1 is that, except for using 4.5162 g of Y2O3 in step (1), the rest is the same as Example 1.

[0127] The chemical formula of the thermal barrier coating material is (Zr0.5 Hf 0.5 ) 0.9 Y 0.1 O 1.95 , and recorded as 10YSHZ.

[0128] Application Example 1

[0129] This application example provides a method for preparing a thermal barrier coating, the preparation method comprising the following steps:

[0130] (I) The thermal barrier coating material obtained in Example 1, a binder and a dispersant were mixed, wherein the binder accounted for 15wt% of the thermal barrier coating material and the dispersant accounted for 20wt% of the thermal barrier coating material. After passing through a 200-mesh sieve, the mixture was sintered at 1200°C for 2h to obtain a bulk density of 2.37g / cm 3 , spray powder with fluidity of 32s / 50g;

[0131] (II) The spray powder obtained in step (I) is subjected to atmospheric plasma spraying, and the spraying parameters are set as voltage 70 V, current 616 A, hydrogen flow rate 53 L / h, argon flow rate 2000 L / h, spraying distance 110 mm, and powder feeding rate 44.5 g / min to obtain a thermal barrier coating.

[0132] Figure 7 This is a differential scanning thermogravimetric curve (TG-DSC) of the thermal barrier coating prepared in Application Example 1 of the present invention. It can be seen from the figure that there is no obvious weight loss in the TG curve and no endothermic or exothermic peak in the DSC curve, indicating that there is no phase change in the heating process and the thermal barrier coating exhibits good phase stability.

[0133] Application Example 2

[0134] This application example provides a method for preparing a thermal barrier coating, the preparation method comprising the following steps:

[0135] (I) The thermal barrier coating material obtained in Example 1, a binder and a dispersant were mixed, wherein the binder accounted for 10 wt % of the thermal barrier coating material, and the dispersant accounted for 10 wt % of the thermal barrier coating material. After passing through a 400 mesh sieve, the mixture was sintered at 1100° C. for 3 h to obtain a bulk density of 1.7 g / cm 3 , spray powder with fluidity of 20s / 50g;

[0136] (II) The spray powder obtained in step (I) is subjected to atmospheric plasma spraying, and the spraying parameters are set as voltage 60 V, current 550 A, hydrogen flow rate 35 L / h, argon flow rate 1500 L / h, spraying distance 90 mm, and powder feeding rate 30 g / min to obtain a thermal barrier coating.

[0137] Application Example 3

[0138] This application example provides a method for preparing a thermal barrier coating, the preparation method comprising the following steps:

[0139] (I) The thermal barrier coating material obtained in Example 1, a binder and a dispersant were mixed, wherein the binder accounted for 20 wt % of the thermal barrier coating material and the dispersant accounted for 20 wt % of the thermal barrier coating material. After passing through a 180 mesh sieve, the mixture was sintered at 1300° C. for 2 h to obtain a bulk density of 3 g / cm 3 , spray powder with fluidity of 55s / 50g;

[0140] (II) The spray powder obtained in step (I) is subjected to atmospheric plasma spraying, and the spraying parameters are set as voltage 80 V, current 650 A, hydrogen flow rate 60 L / h, argon flow rate 2500 L / h, spraying distance 120 mm, and powder feeding rate 50 g / min to obtain a thermal barrier coating.

[0141] Application Example 4

[0142] The difference between this application example and application example 1 is that, except for step (I) using the thermal barrier coating material described in Example 4, the rest is the same as application example 1.

[0143] Figure 8 This is a differential scanning thermogravimetric curve (TG-DSC) of the thermal barrier coating prepared in Application Example 4 of the present invention. It can be seen from the figure that there is no obvious weight loss in the TG curve and no endothermic or exothermic peak in the DSC curve, indicating that there is no phase change in the heating process and the thermal barrier coating exhibits good phase stability.

[0144] Application Example 5

[0145] The difference between this application example and application example 1 is that, except for step (I) using the thermal barrier coating material described in Example 5, the rest is the same as application example 1.

[0146] Fig. 9 This is a differential scanning thermogravimetric curve (TG-DSC) of the thermal barrier coating prepared in Application Example 5 of the present invention. It can be seen from the figure that there is no obvious weight loss in the TG curve and no endothermic or exothermic peak in the DSC curve, indicating that there is no phase change in the heating process and the thermal barrier coating exhibits good phase stability.

[0147] Application Example 6

[0148] The difference between this application example and application example 1 is that, except for step (I) using the thermal barrier coating material described in Example 6, the rest is the same as application example 1.

[0149] Application Example 7

[0150] The difference between this application example and application example 1 is that, except for step (I) using the thermal barrier coating material described in Example 7, the rest is the same as application example 1.

[0151] Application Example 8

[0152] The difference between this application example and application example 1 is that, except for the sintering temperature of step (I) being 1050°C, the rest is the same as application example 1.

[0153] Application Example 9

[0154] The difference between this application example and application example 1 is that, except for the sintering temperature of step (I) being 1350°C, the rest is the same as application example 1.

[0155] Application Example 10

[0156] The difference between this application example and application example 1 is that, except for the hydrogen flow rate of step (II) being 1450 L / h, the rest is the same as application example 1.

[0157] Application Example 11

[0158] The difference between this application example and application example 1 is that, except for the hydrogen flow rate of step (II) being 2550 L / h, the rest is the same as application example 1.

[0159] Application Example 12

[0160] The difference between this application example and application example 1 is that, except for the spraying distance of step (II) being 85 mm, the rest are the same as application example 1.

[0161] Application Example 13

[0162] The difference between this application example and application example 1 is that, except for the spraying distance of step (II) being 125 mm, the rest is the same as application example 1.

[0163] Comparative application example 1

[0164] The only difference between this comparative application example and application example 1 is that, except for step (I) using the thermal barrier coating material described in comparative example 1, the rest is the same as application example 1.

[0165] Fig.10 This is a differential scanning thermogravimetric curve (TG-DSC) of the thermal barrier coating prepared in comparative application example 1 of the present invention. It can be seen from the figure that the TG curve has no obvious weight loss, and the DSC curve has no endothermic or exothermic peak, indicating that there is no phase change during the heating process and the thermal barrier coating exhibits good phase stability.

[0166] Comparative Application Example 2

[0167] The only difference between this comparative application example and application example 1 is that, except for step (I) using the thermal barrier coating material described in comparative example 2, the rest is the same as application example 1.

[0168] Comparative Application Example 3

[0169] The only difference between this comparative application example and application example 1 is that, except for using commercial YSZ thermal barrier coating material directly for atmospheric plasma spraying, the rest is the same as application example 1.

[0170] Figure 3 The 10-80° full spectrum X-ray diffraction patterns of the thermal barrier coatings prepared in Application Example 1, Application Examples 4-5, Comparative Application Example 1 and Comparative Application Example 3 of the present invention are as follows: Figure 4 It is the 27-33° micro-area X-ray step-scanning diffraction pattern of the thermal barrier coating prepared in Application Example 1, Application Examples 4-5, Comparative Application Example 1 and Comparative Application Example 3 of the present invention, Figure 5 It is the 72-76° micro-area X-ray step-scan diffraction pattern of the thermal barrier coating prepared in Application Example 1, Application Examples 4-5, Comparative Application Example 1 and Comparative Application Example 3 of the present invention. It can be seen from the figure that the prepared coating does not contain diffraction peaks of rare earth oxides Yb2O3 and Y2O3, does not contain m phase, and only has a single non-thermodynamically balanced and non-transition metastable tetragonal t' phase;

[0171] Figure 6 The Raman images of the thermal barrier coatings prepared in Application Example 1, Application Examples 4-5, Comparative Application Example 1 and Comparative Application Example 3 of the present invention show that the prepared coatings contain only a single non-thermodynamically balanced and non-transitional metastable tetragonal t' phase;

[0172] Fig.11 This is a differential scanning thermogravimetric curve (TG-DSC) of the thermal barrier coating prepared in comparative application example 3 of the present invention. It can be seen from the figure that there is no obvious weight loss in the TG curve, and there is no endothermic or exothermic peak in the DSC curve, indicating that there is no phase change in the heating process, and the thermal barrier coating exhibits good phase stability;

[0173] Fig.12 The thermal conductivity of the thermal barrier coatings prepared in Application Example 1, Application Examples 4-5, Comparative Application Example 1 and Comparative Application Example 3 of the present invention varies with temperature. It can be seen from the figure that the thermal conductivity increases with increasing temperature from room temperature to 1200°C. At high temperatures, the thermal conductivity of the coating material is always at a low level. The thermal conductivity of the thermal barrier coatings prepared in Application Example 1, Application Examples 4-5 and Comparative Application Example 1 of the present invention is much lower than that in Comparative Application Example 3;

[0174] Fig.13 The density of the thermal barrier coatings prepared in Application Example 1, Application Examples 4-5, Comparative Application Example 1 and Comparative Application Example 3 of the present invention varies with annealing time at 1500°C. It can be seen from the figure that among the prepared coatings, the density change rate after annealing at 1500°C for 24 hours is low, which is much lower than that of Comparative Application Example 3.

[0175] Test Method

[0176] X-ray diffraction patterns and Raman patterns were used to analyze the crystal structures of the thermal barrier coating materials prepared in Example 1, Examples 4-5, and Comparative Example 1 of the present invention and the commercial YSZ thermal barrier coating materials. The crystal structure analysis selected a diffraction angle 2θ range of 10-80° and a Raman shift range of 100-900 cm -1 ;

[0177] The thermal barrier coatings prepared in Example 1, Example 4-5, Comparative Example 1 and Comparative Example 3 were analyzed for their crystal structures using X-ray diffraction patterns and Raman patterns. The diffraction angle 2θ range selected for crystal structure analysis was 10-80°, 27-33°, 72-76°, and the Raman shift range was 100-900cm -1 ; Use simultaneous thermal analysis TG-DSC to characterize whether the thermal barrier coating has phase change, decomposition and other processes in the temperature range from room temperature to 1500℃; Use Archimedes drainage method to measure the density of the thermal barrier coating, use Neumann-Kopp rule to calculate the heat capacity Cp of the thermal barrier coating, use laser thermal conductivity meter to measure the thermal diffusion coefficient, multiply the thermal diffusion coefficient, density and heat capacity to get the thermal conductivity, and then use the porosity correction formula to correct it to get the intrinsic thermal conductivity of the thermal barrier coating;

[0178] The thermal barrier coatings prepared in Example 1-13 and Comparative Example 1-3 were tested for initial density, density after annealing at 1500°C for 12h and 24h, and the anti-sintering performance of the coatings was characterized by the numerical change of density. The test results are recorded in Table 1.

[0179] Table 1

[0180]

[0181]

[0182] The test results show that:

[0183] (1) It can be seen from Application Examples 1-13 and Comparative Application Examples 1-3 that the present invention can improve the high temperature resistance of the thermal barrier coating by continuously dissolving hafnium oxide in zirconium oxide, and improve the melting point and phase transition temperature of the thermal barrier coating. By doping the binary rare earth elements of yttrium and ytterbium, the synergistic effect of the two elements is exerted to improve the thermodynamic properties while also improving the anti-sintering performance of the thermal barrier coating and reducing the thermal conductivity of the thermal barrier coating.

[0184] (2) It can be seen from Application Examples 1 and 4-5 that the thermal barrier coating prepared by the present invention further improves the sintering resistance by further adjusting the doping amount of yttrium and ytterbium.

[0185] (3) It can be seen from Application Examples 1 and 6-7 that the thermal barrier coating prepared by the present invention further improves the anti-sintering performance by further regulating the temperature of the calcination process.

[0186] (4) It can be seen from Application Examples 1 and 8-9 that the thermal barrier coating prepared by the present invention further improves the anti-sintering performance by further regulating the temperature of the sintering process.

[0187] (5) It can be seen from Application Examples 1 and 10-13 that the thermal barrier coating prepared by the present invention further improves the anti-sintering performance by further regulating the hydrogen flow rate and spraying distance during the atmospheric plasma spraying process.

[0188] In summary, the present invention can improve the high temperature resistance of the thermal barrier coating by continuously dissolving hafnium oxide in zirconium oxide, and improve the melting point and phase transition temperature of the thermal barrier coating. By doping the binary rare earth elements of yttrium and ytterbium, the synergistic effect of the two elements is exerted to improve the thermodynamic properties while also improving the anti-sintering performance of the thermal barrier coating and reducing the thermal conductivity of the thermal barrier coating.

[0189] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A thermal barrier coating material, characterized in that: The thermal barrier coating material comprises binary rare earth-doped zirconium-hafnium oxide solid solution powder, wherein the binary rare earth doping elements are yttrium and ytterbium.

2. The thermal barrier coating material according to claim 1, characterized in that: The general chemical formula of the thermal barrier coating material is (Zr 0.5 Hf 0.5 ) 0.9 (Y 1-x Yb x ) 0.1 O 1.95 , where 0.1≤x≤0.

5.

3. A method for preparing a thermal barrier coating material as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: First, a zirconium source, a hafnium source, a yttrium source, a ytterbium source and a solvent are mixed, a precipitant is added dropwise, the mixture is aged, and then a precipitate is obtained by filtering. The precipitate is calcined to obtain the thermal barrier coating material.

4. The preparation method according to claim 3, characterized in that: The zirconium source includes any one of zirconium oxychloride, zirconium chloride or zirconium nitrate, or a combination of at least two thereof; Preferably, the hafnium source includes any one of hafnium chloride, hafnium oxychloride or hafnium nitrate, or a combination of at least two thereof; Preferably, the yttrium source comprises any one of yttrium oxide, yttrium chloride or yttrium nitrate, or a combination of at least two thereof; Preferably, the ytterbium source comprises any one of ytterbium oxide, ytterbium chloride or ytterbium nitrate, or a combination of at least two thereof.

5. The preparation method according to claim 3 or 4, characterized in that: The precipitant includes aqueous ammonia; Preferably, the aging time is 12-24h; Preferably, after aging and before filtering, washing is also included; Preferably, the end point of the washing is to make the pH value of the washing liquid 8-9; Preferably, after filtering and before calcining, washing and drying are also performed in sequence; Preferably, the drying temperature is 60-80°C; Preferably, the drying time is 10-12 hours; Preferably, the calcination temperature is 1000-1200°C; Preferably, the calcination time is 2-4 hours.

6. A thermal barrier coating, characterized in that: The raw material for preparing the thermal barrier coating includes the thermal barrier coating material according to claim 1 or 2.

7. A method for preparing a thermal barrier coating as claimed in claim 6, characterized in that: The preparation method comprises the following steps: secondly mixing the thermal barrier coating material, the binder and the dispersant, sintering to obtain a spraying powder, and performing atmospheric plasma spraying on the spraying powder to obtain the thermal barrier coating; The thermal barrier coating material is the thermal barrier coating material according to claim 1 or 2.

8. The preparation method according to claim 7, characterized in that: The amount of the binder is 10-20wt% of the thermal barrier coating material; Preferably, the amount of the dispersant is 10-20wt% of the thermal barrier coating material; Preferably, the sintering temperature is 1100-1300°C; Preferably, the sintering time is 2-3 hours.

9. The preparation method according to claim 7 or 8, characterized in that: The spraying voltage of the atmospheric plasma spraying is 60-80V; Preferably, the spray gun current of the atmospheric plasma spraying is 550-650A; Preferably, the hydrogen flow rate of the atmospheric plasma spraying is 35-60 L / h; Preferably, the argon gas flow rate of the atmospheric plasma spraying is 1500-2500 L / h; Preferably, the spraying distance of the atmospheric plasma spraying is 90-120 mm; Preferably, the powder feeding rate of the atmospheric plasma spraying is 30-50 g / min.

10. The preparation method according to claim 7, characterized in that: The preparation method comprises the following steps: (1) first mixing a zirconium source, a hafnium source, a yttrium source and a ytterbium source according to a stoichiometric ratio, and then adding a solvent to obtain a clear solution; The temperature of the first mixing is 80-100°C; (2) adding the clarified solution in step (1) dropwise to a precipitant, aging for 12-24 hours, washing with deionized water 5-7 times, wherein the pH of the washing solution after washing is 8-9, and obtaining a white colloidal precipitate; (3) filtering the white colloidal precipitate obtained in step (2), and then washing it with deionized water and ethanol for 3-5 times respectively to obtain a precipitate; (4) drying the precipitate obtained in step (3) at 60-80° C. for 10-12 h, and then grinding, first screening and calcining in sequence to obtain a thermal barrier coating material; The mesh size of the first sieve is 150-250 mesh; the calcination temperature is 1000-1200° C., and the calcination time is 2-4 hours; (5) The thermal barrier coating material, binder and dispersant obtained in the second mixing step (4) are sequentially screened and sintered to obtain a powder for spraying; The mesh number of the second sieve is 180-400 mesh; the sintering temperature is 1100-1300°C, and the sintering time is 2-3h; the bulk density of the spray powder is 1.7-3g / cm 3 , fluidity is 20-55s / 50g; (6) subjecting the spraying powder obtained in step (5) to atmospheric plasma spraying to obtain the thermal barrier coating; The spray gun voltage of the atmospheric plasma spraying is 60-80V, the spray gun current is 550-650A, the hydrogen flow rate is 35-60L / h, the argon flow rate is 1500-2500L / h, the spraying distance is 90-120mm, and the powder feeding rate is 30-50g / min.